Percutaneous surgical treatment of hallux valgus: retrospective study with 6.5-year follow-up - Lara, Luiz; Torres Filho, Lúcio; Cervone, Gabriel; Viana, Rafael; Bordignon, Glaucia; Grajales, Juan; Lancia, Lara (Journal of the Foot & Ankle, 2020)
Objective: To analyze outcomes of hallux valgus surgical correction using the Reverdin-Isham technique by means of clinical and radiographic studies. Methods: We retrospectively assessed 43 feet (38 patients) with moderate to severe hallux valgus treated from June 2009 to July 2014. Mean age at surgery was 59 years; mean postoperative follow-up time was 79 months. Patients were assessed at pre- and postoperative periods both functionally, by the American Orthopaedic Foot and Ankle Society (AOFAS) score, and radiographically, by the hallux valgus angle (HVA), intermetatarsal angle (IMA), distal metatarsal articular angle (DMAA), and shortening of 1st metatarsal bone. Results: AOFAS scores had a mean increase of 55 points. Mean HVA decreased 14.5°, whereas IMA and DMAA exhibited a mean decrease of 3.8° and 9.7°, respectively. Mean shortening of the first metatarsal bone was 3mm. Conclusion: The presented surgical technique showed to be effective to correct mild to moderate hallux valgus, resulting in appropriate angle correction angular and significant increase in AOFAS scores. Level of Evidence IV; Therapeutic Studies; Case Series.